All You Have to Do is Go Out and Do Some Four- and Five-Hour Runs: Understanding Wisconsin's Elite Long Distance Runners, 1975-2011 - Breitbach, Thomas (My University, 2011)
The state of Wisconsin has been the home to numerous national and Olympic level track and field athletes during the 20th and early 21st century. National champions of the high school, collegiate and professional ranks hailed from and trained in Wisconsin. In particular, the state has been well represented by long distance runners in national and international competition, especially since the running boom of the 1970s. This paper aims to understand these individuals, their training, and the impacts that the state of Wisconsin, its climate, its training facilities, its culture, and its people, have had on elite level distance runners.
Keywords: Long distance runners--Wisconsin; Long-distance running--Training--Wisconsin; Long-distance running--Wisconsin